Linking Short-Chain N-Acyl Homoserine Lactone-Mediated Quorum Sensing and Replant Disease: A Case Study of Rehmannia glutinosa - Li, Qian; Wu, Yanhong; Wang, Juanying; Yang, Bo; Chen, Jun; Wu, Hongmiao; Zhang, Zhongyi; Lu, Cuihong; Lin, Wenxiong; Wu, Linkun (Frontiers in Plant Science, 2020)
Rehmannia glutinosa, a perennial medicinal plant, suffers from severe replant disease under consecutive monoculture. The rhizosphere microbiome is vital for soil suppressiveness to diseases and for plant health. Moreover, N-acyl homoserine lactone (AHL)-mediated quorum sensing (QS) regulates diverse behavior in rhizosphere-inhabiting and plant pathogenic bacteria. The dynamics of short-chain AHL-mediated QS bacteria driven by consecutive monoculture and its relationships with R. glutinosa replant disease were explored in this study. The screening of QS bacteria showed that 65 out of 200 strains (32.5%) randomly selected from newly planted soil of R. glutinosa were detected as QS bacteria, mainly consisting of Pseudomonas spp. (55.4%). By contrast, 34 out of 200 (17%) strains from the diseased replant soil were detected as QS bacteria, mainly consisting of Enterobacteriaceae (73.5%). Functional analysis showed most of the QS bacteria belonging to the Pseudomonas genus showed strong antagonistic activities against Fusarium oxysporum or Aspergillus flavus, two main causal agents of R. glutinosa root rot disease. However, the QS strains dominant in the replant soil caused severe wilt disease in the tissue culture seedlings of R. glutinosa. Microbial growth assays demonstrated a concentration-dependent inhibitory effect on the growth of beneficial QS bacteria (i.e., Pseudomonas brassicacearum) by a phenolic acid mixture identified in the root exudates of R. glutinosa, but the opposite was true for harmful QS bacteria (i.e., Enterobacter spp.). Furthermore, it was found that the population of quorum quenching (QQ) bacteria that could disrupt the beneficial P. brassicacearum SZ50 QS system was significantly higher in the replant soil than in the newly planted soil. Most of these QQ bacteria in the replant soil were detected as Acinetobacter spp. The growth of specific QQ bacteria could be promoted by a phenolic acid mixture at a ratio similar to that found in the R. glutinosa rhizosphere. Moreover, these quorum-quenching bacteria showed strong pathogenicity toward the tissue culture seedlings of R. glutinosa. In conclusion, consecutive monoculture of R. glutinosa contributed to the imbalance between beneficial and harmful short-chain AHL-mediated QS bacteria in the rhizosphere, which was mediated not only by specific root exudates but also by the QQ bacterial community.